Development of a search filter for identifying studies completed in primary care - Gill, P. J.; Roberts, N. W.; Wang, K. Y.; Heneghan, C. (Family practice, 2014)
Identifying articles relevant to primary care is challenging for busy clinicians. Setting specific search strategies can be used to help clinicians find pertinent studies in a timely fashion. To develop search filters for identifying research studies of relevance to primary care in MEDLINE (OvidSP). We conducted a search of MEDLINE (OvidSP) for articles published in five core medical journals at five yearly intervals. We identified a gold standard set of primary care relevant articles which was divided into two subsets. The first subset was used to identify frequently occurring words and phrases through textual analysis. Search filters were developed from these words and phrases and internally validated against records in the second subset. We evaluated the filters performance in a search for articles on two common primary care conditions in MEDLINE (OvidSP). Of the 12 045 articles retrieved, 9028 records were reviewed, of which 371 articles were relevant to primary care (gold standard). When the search filters generated from textual analysis were internally validated, filter specificity peaked at 99% with 60% sensitivity, 67% precision and 97% accuracy. When evaluated against a set of articles on two common primary care conditions, the best performing combination search filter specificity maximized at 99.7% with sensitivity reaching 15% (precision 90%; accuracy 89%). The best performing combination search filter works well in reducing the number of irrelevant papers retrieved in a MEDLINE (OvidSP) search if a busy clinician needs to focus on research relevant to primary care.